Unexpected Effects of Aurin Tricarboxylic Acid on Human Platelets - Kinlough-Rathbone, Raelene L; Packham, Marian A (Thrombosis and Haemostasis, 1992)
Aurin tricarboxylic acid (ATA) is a potent inhibitor of ristocetin-mediated platelet agglutination and of shear-induced, von Willebrand factor (vWf)-mediated platelet aggregation, probably via inhibition of vWf interaction with glycoprotein Ib (GPIb). We examined the effects of ATA (both the sodium salt and a solution of ATA in ethanol) on platelet functions in citrated plasma (PRP) and in suspensions of washed platelets in Tyrode-albumin solution (contains 2 mM Ca2+). ATA (42–211 µg/ml) blocked aggregation and release of granule contents induced by thrombin (0.15 U/ml in PRP; 0.03 U/ml in platelet suspension). Responses to higher concentrations of thrombin were not inhibited. ATA also prolonged thrombin-induced clotting of fibrinogen. Since ATA had no effect on fibrinogen-induced responses of chymotrypsin-treated platelets, ATA probably acts on thrombin rather than on fibrinogen.In PRP and platelet suspensions, ATA (acid form 106 µg/ml; sodium salt 122 µg/ml) had little effect on ADP-induced platelet aggregation. The sodium salt of ATA (61–122 µg/ml) enhanced collagen-induced aggregation and release by platelets in citrated plasma and by washed platelets; the enhancement was extensively inhibited by aspirin. With platelet suspensions, ATA significantly enhanced aggregation and release caused by low concentrations of sodium arachidonate (15–50 µM); aggregation and release caused by higher concentrations of arachidonate were somewhat inhibited by ATA. Arachidonate-induced aggregation and release were also enhanced by ATA in PRP. ATA enhanced aggregation and release induced by the calcium ionophore A23187; aspirin had little effect on the enhancement. ATA also enhanced aggregation and release caused by the thromboxane A2 mimetic, U46619 (0.1–.4 µM) or platelet-activating factor (PAF) (5 ng/ ml), but enhancement was never as extensive as when these platelet responses were caused by arachidonate or A23187; aspirin partially inhibited these enhancements. Thus, although ATA may interfere with the interaction of GPIb with large vWf multimers and inhibit the activity of thrombin, thereby having antithrombotic properties, it has potentiating effects on some other agonists; these effects should be considered if it is used as an antithrombotic agent.